2005
DOI: 10.1242/jcs.02431
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminus of prestin influences nonlinear capacitance and plasma membrane targeting

Abstract: Prestin is a unique molecular-motor protein expressed in the lateral plasma membrane of outer hair cells (OHC) in the organ of Corti of the mammalian cochlea. It is thought that prestin undergoes conformational changes driven by the cell's membrane potential. The resulting alterations in OHC-length are assumed to constitute the cochlear amplifier. Prestin is a member of the anion solute carrier family 26 (SCL26A), but it is different from other family members in its unique function of voltage-driven motility. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
90
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(98 citation statements)
references
References 51 publications
7
90
1
Order By: Relevance
“…The specificity of these antibodies has been fully characterized and verified in previous studies, including in prestin knockout mice (Zheng et al, 2001(Zheng et al, , 2005Matsuda et al, 2004). In later experiments, we also used other two commercial anti-prestin Cterminal and N-terminal antibodies (cat#: ss-22694 and ss-22692, respectively, Santa Cruz Biotechnology Inc., CA).…”
Section: Prestin Antibodiesmentioning
confidence: 85%
“…The specificity of these antibodies has been fully characterized and verified in previous studies, including in prestin knockout mice (Zheng et al, 2001(Zheng et al, , 2005Matsuda et al, 2004). In later experiments, we also used other two commercial anti-prestin Cterminal and N-terminal antibodies (cat#: ss-22694 and ss-22692, respectively, Santa Cruz Biotechnology Inc., CA).…”
Section: Prestin Antibodiesmentioning
confidence: 85%
“…4) were cloned into a pEGFP-N2 vector as described previously (16). HEK293T cells were then transfected with the mutated prestin-expressing plasmids, and NLC was measured as described previously (20).…”
Section: Generation Of Prestin Mutants and Evaluation Of Nlc In Hek293tmentioning
confidence: 99%
“…Moreover, a series of short truncations in both cytodomains revealed that, despite normal membrane targeting, these mutations resulted in absent or modified prestin activity both in vitro (Navaratnam et al, 2005;Zheng et al, 2005) and in vivo (Dallos et al, 2008). These functional consequences led the authors to suggest that prestin requires interacting partners to drive OHC motor activity (Navaratnam et al, 2005).…”
Section: Localization Of the Conventional Spectrin Subunits In The Aumentioning
confidence: 99%
“…Previous reports have shown that some particular amino acid residues in the C-terminal region play a key role in prestin cellular distribution and motor activity (Navaratnam et al, 2005;Zheng et al, 2005). We produced two prestin mutants, Del632 and Del709, which have been shown to impair the ability of prestin to confer non-linear capacitance and motility (Zheng et al, 2005). Del632 lacks the STAS motif (sulphate transporter and anti-sigma factor antagonist domain, aa 633-708), a domain identified in all ten SLC26A proteins.…”
mentioning
confidence: 99%